Obstacles in the optimization of bone health outcomes in the female athlete triad - Ducher, G.; Turner, A. I.; Kukuljan, S.; Pantano, K. J.; Carlson, J. L.; Williams, N. I.; de Souza, M. J. (Sports Medicine, 2011)
Maintaining low body weight for the sake of performance and aesthetic purposes is a common feature among young girls and women who exercise on a regular basis, including elite, college and high-school athletes, members of fitness centres, and recreational exercisers. High energy expenditure without adequate compensation in energy intake leads to an energy deficiency, which may ultimately affect reproductive function and bone health. The combination of low energy availability, menstrual disturbances and low bone mineral density is referred to as the `female athlete triad`. Not all athletes seek medical assistance in response to the absence of menstruation for 3 or more months as some believe that long-term amenorrhoea is not harmful. Indeed, many women may not seek medical attention until they sustain a stress fracture.